Association between diabetes mellitus and impaired single-leg stance in patients with chronic liver disease: A cross-sectional study - Kenichi Fudeyasu; Makoto Asaeda; Toshihiro Kawae; Takuo Nomura; Yuki Nakashima; Daisuke Iwaki; Kouki Fukuhara; Takeya Araki; Haruya Ohno; Eisuke Murakami; Shiro Oka; Yukio Mikami (PLoS ONE, 2026)
Diabetes mellitus (DM) is highly prevalent among patients with chronic liver disease (CLD) and is associated with disease progression and complications. However, the impact of DM on physical function, particularly balance, in patients with CLD remains unclear. The aim of this study was to investigate the association between DM and physical function in patients with CLD, with a specific focus on impaired single-leg stance test (SLST). This retrospective study analyzed the medical records of patients with CLD at Hiroshima University Hospital between 2014 and 2017. Logistic regression analysis was performed to identify factors associated with impaired SLST. Receiver operating characteristic curve analysis was conducted to determine cutoff values for predictive factors. The analysis included 152 patients with CLD, of whom 78% had comorbid DM. Patients with DM had a significantly higher prevalence of impaired SLST than those without DM (20% vs. 0%, p = 0.002, Cramer’s V 0.23). In 118 patients with CLD who had comorbid DM, age (odds ratio [OR] 1.089, 95% confidence interval [CI] 1.020–1.177, p = 0.009), body mass index (OR 1.176, 95% CI 1.045–1.343, p = 0.006), and extracellular water-to-total body water ratio (ECW/TBW) (OR 1.065, 95% CI 1.003–1.138, p = 0.039) were significant independent factors associated with impaired SLST (Nagelkerke pseudo- R² 0.31, p < 0.001). The ECW/TBW had the highest predictive accuracy, with a cutoff value of 0.393 (area under the curve = 0.733, sensitivity = 73.9%, specificity = 68.8%). DM was associated with impaired SLST in patients with CLD, suggesting a decline in balance. Age, body mass index, and ECW/TBW are significant predictors of impaired SLST. An ECW/TBW ratio of 0.393 indicates “subclinical” edema in patients with CLD and DM and should be considered in the assessment of fall risk.